Patterns of Natural Selection on Mitochondrial Protein-Coding Genes in Lungless Salamanders: Relaxed Purifying Selection and Presence of Positively Selected Codon Sites in the Family Plethodontidae - Ryosuke Kakehashi; Atsushi Kurabayashi (International Journal of Genomics)
There are two distinct lungless groups in caudate amphibians (salamanders and newts) (the family Plethodontidae and the genus Onychodactylus, from the family Hynobiidae). Lunglessness is considered to have evolved in response to environmental and/or ecological adaptation with respect to oxygen requirements. We performed selection analyses on lungless salamanders to elucidate the selective patterns of mitochondrial protein-coding genes associated with lunglessness. The branch model and RELAX analyses revealed the occurrence of relaxed selection (an increase of the dN/dS ratio=ω value) in most mitochondrial protein-coding genes of plethodontid salamander branches but not in those of Onychodactylus. Additional branch model and RELAX analyses indicated that direct-developing plethodontids showed the relaxed pattern for most mitochondrial genes, although metamorphosing plethodontids had fewer relaxed genes. Furthermore, aBSREL analysis detected positively selected codons in three plethodontid branches but not in Onychodactylus. One of these three branches corresponded to the most recent common ancestor, and the others corresponded with the most recent common ancestors of direct-developing branches within Hemidactyliinae. The positive selection of mitochondrial protein-coding genes in Plethodontidae is probably associated with the evolution of direct development.